Three Objectives of International banking Regulation: Analysis of Their Interrelationship and Issues - E. P. Dzhagityan; O. R. Mukhametov (Финансы: теория и практика, 2023)
In response to the Global Financial Crisis of 2008–2009, international financial regulators tightened the regime of banking supervision in order to minimize systemic risks, strengthen banking sector resilience and ensure financial stability. Given the increased level of credit risks and the issue of liquidity in the banking sector, as well as the role of banks in promoting the dynamics of the macro-environment, the objectives of banking regulation, through their interrelationship, may conflict with one another, and the research of this phenomenon is the subject of this article. The academic literature excludes research that provides definitive evidence on whether post-crisis banking regulation reform has achieved each of the abovementioned goals, determining the relevance of our study. The scientific novelty is attributed to the principally different approach proposed by the authors in assessing the effectiveness of the post-crisis model of international banking regulation, which is based on the analysis of the interaction and contradictions of the objectives of modern regulatory policy. The purpose of the study is to identify the extent to which the objectives of the post-crisis regulatory model were achieved and to what extent regulatory efforts contribute to the reduction of systemic risks. To achieve the research objectives, the authors applied methods of statistical and comparative analysis, synthesis of factors underlying the post-crisis regulatory mechanism, systematization, generalization and forecasting. The authors analyzed the main elements of the regulatory reform, examined the dynamics of the banking sector, and assessed the impact of the reform on systemic risks and economic growth. The research results show that tighter supervisory standards strengthened bank stress resilience, reduced systemic risks, and had a limited impact on economic growth. The article concludes that the objectives of banking regulation actively interact, but do not conflict: a consistent transition to the new Basel III standards allows each objective to be achieved.